Advertising for Europe. TV ads during the 2009 European election campaign in four countries - Holtz-Bacha, Christina; Johansson, Bengt; Leidenberger, Jacob; Maarek, Philippe; Merkle, Susanne (Nordicom Review, 2012)
This study analyzes and compares party ads that were broadcast on television during the 2009 European Election campaign in France, Germany, Sweden and the UK. Even though electoral TV ads have never reached the same importance in European countries as in the US, such ads are to be regarded as an expression of the specific political culture of a country and therefore have relevance beyond election campaigns. An international comparison of ads produced for the same event is particularly suited to revealing similarities across cultures as well as national idiosyncrasies. Additionally, the present study demonstrates a methodological approach that defines a 'sequence' as the unit of analysis instead of the whole spot, and thus it is different from previous research on electoral advertising.
WiSo-Import:2015-03-26:4165
Keywords: electoral advertising; European election; content analysis; international com-parison

Allemagne: Une campagne qui n'en est pas une - Holtz-Bacha, Christina; Leidenberger, Jacob (La communication politique européenne sans l'Europe. Les élections au Parlement européen de 2009, 2012)
WiSo-Import:2015-04-20:3369

Bambi und der böse Wolf. Ségolene Royal und der französische Präsidentschaftswahlkampf in der deutschen und französischen Presse - Leidenberger, Jacob; Holtz-Bacha, Christina; Koch, Thomas (Frauen, Politik und Medien, 2008)
UnivIS-Import:2015-04-20:Pub.2008.rw.fbwiwi.LKP.bambiu

Europawahl 2009: Wahlkampf im Schatten der Bundestagswahl oder doch eine europäische Kampagne? - Holtz-Bacha, Christina; Leidenberger, Jacob (Die Massenmedien im Wahlkampf. Das Wahljahr 2009, 2010)
WiSo-Import:2015-04-20:926
Keywords: Transformation

La représentation des candidats à élection présidentielle dans la presse allemande - Leidenberger, Jacob; Merkle, Susanne; Holtz-Bacha, Christina (Présidentielle 2012: une communication politique bien singulière, 2013)
Keywords: Präsidentschaftswahl; Frankreich; Inhaltsanalyse; Politische Kommunikation; Berichterstattung; Presse

La représentation des candidats á l'élection présidentielle dans la presse allemande. - Holtz-Bacha, Christina; Leidenberger, Jacob; Merkle, Susanne (Présidentielle 2012: une communication politique bien singulière, 2013)
WiSo-Import:2015-04-20:5035

Merkel-Schroeder, Royal-Sarkozy, genre et élections vus par la presse allemande et française - Holtz-Bacha, Christina; Koch, Thomas; Leidenberger, Jacob (La communication politique de la présidentielle de 2007, 2009)
WiSo-Import:2015-04-20:1514
Keywords: Transformation; Merkel-Schroeder Royal-Sarkozy genre et élections vus par la presse allemande et française